The Effectiveness of Technology Integration by Redefinition in Teaching Asian History among Grade 7 Learners in a Catholic School - Angelica V. Alison; Dexter Paul D. Dioso (Philippine Social Science Journal, 2025)
Technology plays a pivotal role in education by enabling innovative teaching methods. Anchored in the Technological Pedagogical Content Knowledge (TPACK) framework, this study assessed the effectiveness of the Substitution, Augmentation, Modification, and Redefinition (SAMR) model’s "Redefinition" level in teaching Asian History to Grade 7 learners at a Catholic school on Negros Island. Utilizing a quasi-experimental design, the research compared a control group receiving conventional instruction with an experimental group benefiting from redefined technology-integrated strategies. The results demonstrated a statistically significant improvement in the academic performance of the experimental group. These findings confirm that integrating technology at the redefinition level moves beyond simple substitution, significantly enhancing learner engagement, comprehension, and overall academic achievement.